Experimental study on local heat transfer and hydrodynamics with single tube and tube bundles in an external heat exchanger. (25th February 2019) - Cai, Runxia; Zhang, Man; Ge, Rongcun; Zhang, Xian; Cai, Jin; Zhang, Yi; Huang, Yiqun; Yang, Hairui; Lyu, Junfu
Highlights: An EHE test rig with the cross section of 1.2 m × 0.8 m was established. Local heat transfer coefficients with single tube and tube bank were measured. Correlation between bubble frequency and heat transfer coefficients was analyzed. The non-uniform heat transfer phenomenon in EHEs was explained. Effect of solid mass flow rate on heat transfer coefficients was studied. Abstract: External heat exchangers (EHEs) are widely used in many industrial fields for heat absorption, such as circulating fluidized bed combustion, solar energy generation, etc. However, considerable deviation of tube wall temperatures was found in the commercial EHEs, which will result in the overheating of tubes and affect the safe operation. In order to investigate the non-uniform heat transfer phenomenon, local heat transfer and hydrodynamics with a horizontal tube and a vertical tube as well as tube bundles were measured in an EHE with the cross section of 1.2 m × 0.8 m. The experimental results showed that for the single tube heat transfer, a bimodal distribution of the heat transfer coefficients was gradually converted to a unimodal distribution with the increase in the fluidizing velocity, and the similar spatial distribution was also observed for the bubble frequency, which indicated that the low bubble frequency in the wall regions caused the non-uniform distribution of the heat transfer coefficients. Additionally, the solid mass flow rate significantly increased the heat transfer coefficients near the bed surface due to the rising bed height, but had a minor impact on the results in other areas. For the arrangement of tube bundles, the unimodal distribution of the heat transfer coefficients and the bubble frequency was accelerated to emerge at low fluidizing velocities, so the heat transfer coefficients near the side walls were always lower than those in the central region.